2020
DOI: 10.1002/asia.201901721
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Engineering of Nanomaterials Derived from Prussian Blue and Its Analogs for Electrochemical Water Splitting

Abstract: Electrochemical water splitting (EWS) is a sustainable and promising technology for producing hydrogen as an ideal energy carrier to address environmental and energy issues. Developing highly‐efficient electrocatalysts for hydrogen and oxygen evolution reactions (HER and OER) is critical for increasing the efficiency of water electrolysis. Recently, nanomaterials derived from Prussian blue (PB) and its analogs (PBA) have received increasing attention in EWS applications owing to their unique composition and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…[278] It can also be mentionned that they can be converted into many other interesting compounds relevant for such application. [279] However, despite much progress has been made, there are very few PBAs and their derived materials that combine the advantages of all performance indicators such as facile preparation, low-cost, excellent electrochemical performance including tow overpotential, hich catalytic current density, and high stability. [280] In connection with the search for alternative solutions to these limitations, several discrete nanoheterostructures combining PBAs, such as MnFe-PBA, [251] CoFe-PBA, [195], [236], [281] or NiFe-PBA [195], [196], [281] with other inorganic materials for instance gold, [281] platinum, [195], [196] CoS2 [236] or POM [251] were developed to afford such active electrocatalysts for OER [236] [195] [251] or HER.…”
Section: Iii11 Supercapacitorsmentioning
confidence: 99%
“…[278] It can also be mentionned that they can be converted into many other interesting compounds relevant for such application. [279] However, despite much progress has been made, there are very few PBAs and their derived materials that combine the advantages of all performance indicators such as facile preparation, low-cost, excellent electrochemical performance including tow overpotential, hich catalytic current density, and high stability. [280] In connection with the search for alternative solutions to these limitations, several discrete nanoheterostructures combining PBAs, such as MnFe-PBA, [251] CoFe-PBA, [195], [236], [281] or NiFe-PBA [195], [196], [281] with other inorganic materials for instance gold, [281] platinum, [195], [196] CoS2 [236] or POM [251] were developed to afford such active electrocatalysts for OER [236] [195] [251] or HER.…”
Section: Iii11 Supercapacitorsmentioning
confidence: 99%
“…Despite widely used MOFs such as ZIF [22,24,25] and MIL [26,27] as precursors, Prussian blue analogues (PBAs) are a kind of MOF with a relatively low price. It has been demonstrated that the construction of three-dimensional (3D) architectures from TMC nanomaterials prepared with PBAs as a template also effectively boosted the HER activity due to their relative abundance of highly active sites brought about by high porosity [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, the sluggish four electrons process of OER still hinders the practical applications of new energy technology in green and sustainable energy conversion and energy storage. [1,2] In this regard, the exploration of highly efficient and affordable OER catalysts is of great significance. Generally, precious metal materials such as iridium (Ir), ruthenium (Ru) and their oxides (IrO 2 and RuO 2 ) are recognized as highly active catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen evolution reaction (OER) is of vital importance for the development of metal‐air batteries, electrochemical water splitting and fuel cells. However, the sluggish four electrons process of OER still hinders the practical applications of new energy technology in green and sustainable energy conversion and energy storage [1,2] . In this regard, the exploration of highly efficient and affordable OER catalysts is of great significance.…”
Section: Introductionmentioning
confidence: 99%